Salience in Second Language Acquisition: Physical Form, Learner Attention, and Instructional Focus - Cintrón-Valentín, Myrna C.; Ellis, Nick C. (Frontiers in Psychology, 2016)
We consider the role of physical form, prior experience, and form focused instruction (FFI) in adult language learning. (1) When presented with competing cues to interpretation, learners are more likely to attend to physically more salient cues in the input. (2) Learned attention is an associative learning phenomenon where prior-learned cues block those that are experienced later. (3) The low salience of morphosyntactic cues can be overcome by FFI, which leads learners to attend cues which might otherwise be ignored. Experiment 1 used eye-tracking to investigate how language background influences learners’ attention to morphological cues, as well as the attentional processes whereby different types of FFI overcome low cue salience, learned attention and blocking. Chinese native speakers (no L1 verb-tense morphology) viewed Latin utterances combining lexical and morphological cues to temporality under control conditions (CC) and three types of explicit FFI: grammar instruction (VG), verb salience with textual enhancement (VS), and verb pretraining (VP), and their use of these cues was assessed in a comprehension test. CC participants were significantly more sensitive to the adverbs than verb morphology. Instructed participants showed greater sensitivity to the verbs. These results reveal attentional processes whereby learners’ prior linguistic experience can shape their attention toward cues in the input, and whereby FFI helps learners overcome the long-term blocking of verb-tense morphology. Experiment 2 examined the role of modality of input presentation – aural or visual – in L1 English learners’ attentional focus on morphological cues and the effectiveness of different FFI manipulations. CC participants showed greater sensitivity toward the adverb cue. FFI was effective in increasing attention to verb-tense morphology, however, the processing of morphological cues was considerably more difficult under aural presentation. From visual exposure, the FFI conditions were broadly equivalent at tuning attention to the morphology, although VP resulted in balanced attention to both cues. The effectiveness of morphological salience-raising varied across modality: VS was effective under visual exposure, but not under aural exposure. From aural exposure, only VG was effective. These results demonstrate how salience in physical form, learner attention, and instructional focus all variously affect the success of L2 acquisition.